2009
DOI: 10.1038/sj.bjc.6604889
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infections and reduced risk of bladder cancer in Los Angeles

Abstract: We investigated the association between urinary tract infections (UTIs) and transitional cell carcinoma of the bladder in a populationbased case -control study in Los Angeles covering 1586 cases and age-, gender-, and race-matched neighbourhood controls. A history of bladder infection was associated with a reduced risk of bladder cancer among women (odds ratio (OR), 0.66; 95% confidence interval (CI), 0.46 -0.96). No effect was found in men, perhaps due to power limitations. A greater reduction in bladder canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…Furthermore, consistent with the risk factors described in other studies [8][9][10][11][12], age, male sex, urinary tract infection or stones, and nephropathy were significant risk factors (Tables 1 and 2). A recent population-based matched case-control study performed in the USA suggested a reduced risk of bladder cancer in women, but not in men, with a history of urinary tract infection [13]. Actually, when men and women were analysed separately, nephropathy and urinary tract diseases including infection and stones remained significant in both sexes (data not shown).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, consistent with the risk factors described in other studies [8][9][10][11][12], age, male sex, urinary tract infection or stones, and nephropathy were significant risk factors (Tables 1 and 2). A recent population-based matched case-control study performed in the USA suggested a reduced risk of bladder cancer in women, but not in men, with a history of urinary tract infection [13]. Actually, when men and women were analysed separately, nephropathy and urinary tract diseases including infection and stones remained significant in both sexes (data not shown).…”
Section: Discussionmentioning
confidence: 88%
“…The discrepancy between men and women in the study performed in the USA and between the study performed in the USA and the present study is attributable to the inherent limitations of the case-control design of the USA study or to the different ethnicities of the individuals in the respective studies. Therefore the lower risk in the US women with urinary tract infection [13] requires confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the association, if it exists, is limited to squamous cell carcinomas only and that including transitional cell carcinomas in the analyses obscures the findings through misclassification. Potential confounders such as the antitumor effects of NSAIDs or antibiotics used by patients may also need to be assessed (125).…”
Section: Alterations Of Normal Host Responses Chronic Inflammationmentioning
confidence: 99%
“…4,5 In Egypt, carcinoma of the bladder is the most prevalent cancer, accounting for as many as 31% of all cancer cases. Currently, it ranks first in males representing 16.2 % of male cancer.…”
Section: Introductionmentioning
confidence: 99%